Optical genome mapping reveals additional prognostic information compared to conventional cytogenetics in AML/MDS patients. Issue 12 (7th February 2022) - Gerding, Wanda M.; Tembrink, Marco; Nilius‐Eliliwi, Verena; Mika, Thomas; Dimopoulos, Fotios; Ladigan‐Badura, Swetlana; Eckhardt, Matthias; Pohl, Michael; Wünnenberg, Max; Farshi, Pakhshan; Reimer, Peter; Schroers, Roland; et al.
Abstract: Cytogenetic diagnostics play a crucial role in risk stratification and classification of myeloid malignancies such as acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS), thus influencing treatment decisions. Optical genome mapping (OGM) is a novel whole genome method for the detection of cytogenetic abnormalities. Our study assessed the applicability and practicality of OGM as diagnostic tool in AML and MDS patients. In total, 27 patients with AML or MDS underwent routine diagnostics including classical karyotyping and fluorescence in situ hybridization (FISH) or real‐time PCR analysis wherever indicated as well as OGM following a recently established workflow. Methods were compared regarding concordance and content of information. In 93%, OGM was concordant to classical karyotyping and a total of 61 additional variants in a predefined myeloid gene‐set could be detected. In 67% of samples the karyotype could be redefined by OGM. OGM offers a whole genome approach to cytogenetic diagnostics in AML and MDS with a high concordance to classical cytogenetics. The method has the potential to enter routine diagnostics as a gold standard for cytogenetic diagnostics widely superseding FISH. Furthermore, OGM can serve as a tool to identify genetic regions of interest and future research regarding tumor biology. Abstract : What's new? Cytogenetic diagnostics are essential for the classification and treatment of patients with hematological malignancies. This study assessed the applicability and practicality of the novel optical genome mapping methodology as a diagnostic tool in acute myeloid leukemia and myelodysplastic syndrome patients. The results show that OGM offers substantial advantages over conventional cytogenetic methods for structural variant detection by providing detailed and new genetic information on a genome‐wide level. The new approach could potentially improve clinical diagnosis and add novel insights on disease mechanisms.